2017
DOI: 10.1371/journal.pntd.0005630
|View full text |Cite
|
Sign up to set email alerts
|

First report of naturally infected Aedes aegypti with chikungunya virus genotype ECSA in the Americas

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 39 publications
10
46
0
Order By: Relevance
“…The same genotype was detected in Ae. aegypti collected in Sergipe and represented the first report in Brazil and in the Americas [87], and in human samples from Alagoas, Bahia, Paraíba, and Sergipe [88][89][90].…”
Section: Discussionmentioning
confidence: 94%
“…The same genotype was detected in Ae. aegypti collected in Sergipe and represented the first report in Brazil and in the Americas [87], and in human samples from Alagoas, Bahia, Paraíba, and Sergipe [88][89][90].…”
Section: Discussionmentioning
confidence: 94%
“…More recently, with the first isolation in Brazil of the Chikungunya virus (CHIKV) in September, 2014, in the city of Oiapoque ‐ Amapá (Teixeira et al ) and of the Zika virus (ZIKV) in 2015 in the city of Camaçari – Bahia (Campos et al ), Ae. aegypti received still greater notoriety, as it was once again indicated as the principal vector of these etiological agents to human beings, naturally infected specimens already having been found (Ferreira‐de‐Brito et al , Costa‐da‐Silva et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Although CHIKV ECSA has been found only in Ae. aegypti mosquitoes ( 9 ), a recent study has shown that Ae. albopictus mosquitoes in Brazil are also highly competent in CHIKV ECSA transmission ( 10 ).…”
mentioning
confidence: 99%